Potentials and challenges of Levodopa particle formulation for treatment of Parkinson's disease through intranasal and pulmonary delivery - Paul, Mahasweta (2022)
Inhalation drug delivery has gained interests in delivery of Levodopa for the treatment of Parkinson's disease. In comparison to traditional oral delivery, delivery via intranasal or pulmonary pathways allows a slower drug degradation, greater drug bioavailability, increased blood plasma concentrations for longer periods and the ability to bypass the blood brain barrier. This review aims to highlight and summarize the recent advances made in the development of Levodopa particle formulations in terms of its characteristics, production techniques, choice of carrier materials, as well as pharmacokinetics and pharmacodynamics the formulations.